2020
DOI: 10.3389/fnhum.2020.00250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cTBS on the Frequency-Following Response and Other Auditory Evoked Potentials

Abstract: The frequency-following response (FFR) is an auditory evoked potential (AEP) that follows the periodic characteristics of a sound. Despite being a widely studied biosignal in auditory neuroscience, the neural underpinnings of the FFR are still unclear. Traditionally, FFR was associated with subcortical activity, but recent evidence suggested cortical contributions which may be dependent on the stimulus frequency. We combined electroencephalography (EEG) with an inhibitory transcranial magnetic stimulation prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 120 publications
(164 reference statements)
0
6
0
Order By: Relevance
“…Thus, the orientation and location of intracranial current densities induced by tDCS were not optimized for neuromodulation of lower auditory brain areas (i.e., brainstem). However, we note that even with more optimal foci for auditory neuromodulation (e.g., superior temporal lobe), the effects of magnetic (TMS) and current (tDCS) stimulation on FFRs remains equivocal ( López-Caballero et al, 2020 ; Mai and Howell, 2021 ). For example, continuous theta burst TMS over right auditory cortex fails to yield measurable changes in FFRs suggesting deeper, more peripheral sources (i.e., brainstem) which are insensitive to cortical stimulation ( López-Caballero et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, the orientation and location of intracranial current densities induced by tDCS were not optimized for neuromodulation of lower auditory brain areas (i.e., brainstem). However, we note that even with more optimal foci for auditory neuromodulation (e.g., superior temporal lobe), the effects of magnetic (TMS) and current (tDCS) stimulation on FFRs remains equivocal ( López-Caballero et al, 2020 ; Mai and Howell, 2021 ). For example, continuous theta burst TMS over right auditory cortex fails to yield measurable changes in FFRs suggesting deeper, more peripheral sources (i.e., brainstem) which are insensitive to cortical stimulation ( López-Caballero et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…However, we note that even with more optimal foci for auditory neuromodulation (e.g., superior temporal lobe), the effects of magnetic (TMS) and current (tDCS) stimulation on FFRs remains equivocal ( López-Caballero et al, 2020 ; Mai and Howell, 2021 ). For example, continuous theta burst TMS over right auditory cortex fails to yield measurable changes in FFRs suggesting deeper, more peripheral sources (i.e., brainstem) which are insensitive to cortical stimulation ( López-Caballero et al, 2020 ). In contrast, Mai and Howell (2021) showed that tDCS neurostimulation over right auditory cortex can cause subtle decreases in speech-FFR amplitudes (i.e., F0 coding), though apparently without concomitant changes in pitch discrimination behavior ( Mai and Howell, 2021 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our current results warrant further research that directly compares the lateralization of right versus left MT+ stimulation effects on MOT. Second, although we used fMRI guided neuronavigation to target cTBS, we cannot rule out the possibility that cTBS effects propagated to surrounding cortical areas and/or altered activity (Casula et al, 2016;L opez-Caballero et al, 2020;Rocchi et al, 2018) in other nodes of the neural network involved in MOT. Third, because we did not include a low-level motion control task, we do not know the extent to which motion processing deficits per se were involved in reduced MOT task performance following active MT+ cTBS.…”
Section: Resultsmentioning
confidence: 99%
“…FFRs are scalp-recorded potentials reflecting a mixture of phase locked activity from several nuclei along the auditory pathway (Smith et al 1975;Sohmer et al 1977;Skoe and Kraus 2010;. Though cortex can contribute to FFRs under limited circumstances (Coffey, Herholz, et al 2016), speech-FFRs are dominantly generated by midbrain sources (i.e., inferior colliculus, IC) when recorded via EEG using high (> 150 Hz) fundamental frequency stimuli (Kiren et al 1994;López-Caballero et al 2020;Bidelman and Momtaz 2021;Gorina-Careta et al 2021;Price and Bidelman 2021). While the IC is likely too early along the processing hierarchy to show bottom-up, categorical organization de novo, top-down influences from cortex via the descending corticofugal system (Gao and Suga 1998) could modulate brainstem speech representations to produce categorical encoding effects as was recently observed in human FFRs (Price and Bidelman 2021;Lai et al 2022;Carter and Bidelman 2023;Lai et al 2023).…”
mentioning
confidence: 99%